Cerebroarterial pulsatility and resistivity indices are associated with cognitive impairment and white matter hyperintensity in elderly subjects: A phase-contrast MRI study. Issue 3 (March 2021) - Pahlavian, Soroush H; Wang, Xinhui; Ma, Samantha; Zheng, Hong; Casey, Marlena; D'Orazio, Lina M; Shao, Xingfeng; Ringman, John M; Chui, Helena; Wang, Danny JJ; Yan, Lirong
Increased cerebroarterial pulsations are thought to be contributing factors in microvascular damage and cognitive impairment. In this study, we assessed the utility of two-dimensional (2D) phase-contrast MRI (PC-MRI) in quantifying cerebroarterial pulsations and evaluated the associations of pulsatile and non-pulsatile hemodynamic measures with cognitive performance and white matter hyperintensities (WMH). Neurocognitive assessments on 50 elderly subjects were performed using clinical dementia rating (CDR) and Montreal cognitive assessment (MoCA). An electrocardiogram-gated 2D PC-MRI sequence was used to calculate mean flow rate, pulsatility index (PI), and resistivity index (RI) of the internal carotid artery. For each subject, whole brain global cerebral blood flow (gCBF) and relative WMH volume were also quantified. Elevated RI was significantly associated with reduced cognitive performance quantified using MoCA ( p  =   0.04) and global CDR ( p  =   0.02). PI and RI were both significantly associated with relative WMH volume ( p  =   0.01, p  <   0.01, respectively). However, non-pulsatile hemodynamic measures were not associated with cognitive impairment or relative WMH volume. This study showed that the cerebroarterial pulsatile measures obtained using PC-MRI have stronger association with the measures of cognitive impairment compared to global blood flow measurement and as such, might be useful as potential biomarkers of cerebrovascular dysfunction in preclinical populations.